Antimicrobial agents of plant origin for the treatment of phlogistic-infectious diseases of the lower female genital tract - Francesco Gon; Fabrizia Gionechetti; Linda Furlanis; Lucia Corich; Cristina Lagatolla; Cinzia Sanna; Mauro Ballero; Silvio Sosa; Roberto Della Loggia; Enrico Angelo Tonin (Microbiologia Medica, 2012)
The phlogistic-infectious diseases of the lower female genital tract are one of the most widespread obstetricgynecologic issues, due to treatment failures that cause frequent relapses and to the adverse effects of some commonly used drugs.The most common vaginal syndromes are due to uncontrolled growth of bacteria or fungi which replace the normal vaginal flora, causing phlogistic and infectious based diseases. These infections are treated with anti-inflammatory and antibiotic therapy; however, the emergence of resistant strains and the ability of many microorganisms to grow inside biofilms severely reduce the repertoire of useful agents.Thus, in the last years increasing interest has been focused toward compounds of plant origin with anti-microbial properties. In the present work, we studied the antimicrobial activity of fractions obtained from endemic plants of Sardinia towards microorganisms that frequently are involved in vaginal infectious diseases: Streptococcus agalactiae, Gardnerella vaginalis and Candida albicans.